Antecedents and Contingent Effects of Organizational Adaptive Capability on Firm Product Innovativeness - Akgun, Ali E.; Keskin, Halit; Byrne, John (Wiley, 2012)
Organizational adaptive capability is a broad term and was studied from different perspectives, such as market, technology, and management system, in the management literature. However, the simultaneous effects of these different perspectives and their related adaptive capability constructs on a firm's product innovativeness have yet to be addressed. Additionally, an empirical study of the influence of informal structural dimensions, such as loose coupling, multiplexity, and redundancy, on the organizational adaptive capability, as antecedents, is also missing in the technology and innovation management (TIM) literature. By studying 153 firms, we found that (1) market-, technology-, and management system-related adaptive capability constructs simultaneously and positively impact firm product innovativeness; (2) under the loose coupling construct, autonomous behaviors of departments positively impact technology and management system adaptive capability, loose management style influences market and management system adaptive capability, and uneven/slow information travel in organizations negatively affects technology and management system adaptive capability; (3) multiplexity positively influences all organizational adaptive capability constructs; and (4) under the redundancy construct, information distribution redundancy has an n shape relationship with technology adaptive capability. We also demonstrated that the impact of informal structural constructs on adaptive capability is contingent upon environmental turbulence, e.g., rapid or unanticipated changes in market and technology. We found that the influence of loose management style on technology adaptive capability decreases with increased rate of market turbulence, and the effect of resource slack, as a part of the redundancy construct, on technology adaptive capability changes quadratically, an n shaped curve, with an increased rate of market turbulence. We further found that the effect of the autonomous behaviors of departments on market adaptive capability increases with an increased level of technology turbulence. The role of resource slack on the market adaptive capability was also found to change quadratically, an n shaped curve, with an increased rate of technology turbulence. Interestingly, the impact of the information distribution redundancy on market adaptive capability changes nonlinearly, a U shaped curve, with an increased rate of technology turbulence. Further, we showed that the influence of organizational technology adaptive capability on product innovativeness increases with increased level of technology turbulence. This study concludes with several theoretical and managerial implications.
Keywords: Dynamic Capabilities; Management; Adaptation; Behavior; Market; Trust; Adaptability; Assimilation; Uncertainty; Sensemaking